2015
DOI: 10.2147/ndt.s56107
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve medication adherence in patients with schizophrenia: the role of support services

Abstract: The purpose of this review is to describe research over the past 10 years on the role of support services in promoting medication adherence in mental health consumers diagnosed with schizophrenia. A literature search was conducted using the terms “medication adherence,” “schizophrenia,” and “support services,” using Medline, PubMed, and CINAHL. Reference lists from published studies were also reviewed to identify additional research studies. Twenty-two articles focused on support-service intervention studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 64 publications
3
55
0
2
Order By: Relevance
“…Further exploring the behavioural and environmental determinants associated with diabetes medication adherence in schizophrenia would inform the creation of rigorous interventions (e.g. providing patients with detailed instructions and concrete problem-solving strategies such as reminders, self-monitoring tools, cues, reinforcements) (El-mallakh and Findlay et al, 2015). For instance, a review by El-Mallakh and Findlay (2015) points to various family and clinician support services that are available to help patients with schizophrenia better adhere to their medication (Zygmunt et al, 2002).…”
Section: Diabetes Medication Adherence In Schizophrenia 23mentioning
confidence: 99%
See 1 more Smart Citation
“…Further exploring the behavioural and environmental determinants associated with diabetes medication adherence in schizophrenia would inform the creation of rigorous interventions (e.g. providing patients with detailed instructions and concrete problem-solving strategies such as reminders, self-monitoring tools, cues, reinforcements) (El-mallakh and Findlay et al, 2015). For instance, a review by El-Mallakh and Findlay (2015) points to various family and clinician support services that are available to help patients with schizophrenia better adhere to their medication (Zygmunt et al, 2002).…”
Section: Diabetes Medication Adherence In Schizophrenia 23mentioning
confidence: 99%
“…providing patients with detailed instructions and concrete problem-solving strategies such as reminders, self-monitoring tools, cues, reinforcements) (El-mallakh and Findlay et al, 2015). For instance, a review by El-Mallakh and Findlay (2015) points to various family and clinician support services that are available to help patients with schizophrenia better adhere to their medication (Zygmunt et al, 2002). These services include multi-cultural education workshops, mobile-and computer-based technologies, reminder Diabetes medication adherence in schizophrenia 24 phone calls, motivational interviewing, cognitive behavioural therapy, as well as home visits.…”
Section: Diabetes Medication Adherence In Schizophrenia 23mentioning
confidence: 99%
“…The monitoring of levels of FLU in plasma and its relationship with the clinical response are not widely discussed in the literature, although it was reported that plasma levels were not appropriate for predicting drug maintenance therapy (Brunswick et al, ). It is known that adherence to the treatment also depends on the patient recognizing the need for medication and being committed with the treatment, and there being no financial constraints (El‐Mallakh & Findlay, ); adherence has a linear relationship with the plasma concentrations. The obtained values demonstrate that, although the dosages of FLU differed, the plasma levels were similar, the higher dosage having a lower plasma level.…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, El-Mallakh et al [42] reviewed the prior ten years of research on the role of support services in promoting medication adherence in people with schizophrenia, and suggested that adherence interventions should be tailored to the specific needs of each person, stressed the importance of conducting a root-cause analysis of reasons for non-adherence in each person prior to implementation of services, and recommended addressing adherence to psychiatric medication as a primary goal with adherence to medication for medical illness as a secondary goal. More specific suggestions include interventions with technological supports and environmental cues.…”
Section: Discussionmentioning
confidence: 99%